2020
DOI: 10.2174/1570159x17666191101125530
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Interventions in Neurological Disorder Therapeutics by Regulating Glutamate Signaling

Abstract: Glutamate is the major excitatory neurotransmitter in the central nervous system, and its signaling is critical for excitatory synaptic transmission. The well-established glutamate system involves glutamate synthesis, presynaptic glutamate release, glutamate actions on the ionotropic glutamate receptors (NMDA, AMPA, and kainate receptors) and metabotropic glutamate receptors, and glutamate uptake by glutamate transporters. When the glutamate system becomes dysfunctional, it contributes to the pathogenesis of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 158 publications
(168 reference statements)
2
32
0
Order By: Relevance
“…To date, no data documenting the effect of ISL on glutamate release was available. Several reports have indicated that natural products may effectively reduce the release of glutamate [20][21][22][23]. We examined whether ISL exhibited an effect on glutamate release in rat cerebrocortical nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no data documenting the effect of ISL on glutamate release was available. Several reports have indicated that natural products may effectively reduce the release of glutamate [20][21][22][23]. We examined whether ISL exhibited an effect on glutamate release in rat cerebrocortical nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduced glutamatergic transmission through the inhibition of released glutamate has been proposed as a neuroprotective mechanism [17][18][19]. Studies have reported that several natural products with neuroprotective effects may reduce presynaptic glutamate release [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related brain disorders, such as dementia and its most prevalent form Alzheimer’s disease, are a burden with limited pharmacological therapies available [ 5 ]. Multiple mechanisms have been proposed to underlie the causes of dementia, and therefore there are a variety of potentially valid treatment strategies from the broad concepts of improving angiogenesis and cerebral blood flow [ 6 ] or the antioxidant and neuroprotective effect against oxidative stress [ 7 ], to more specific targets such as modulating the brain glutamatergic and cholinergic neurotransmission [ 8 ] or improving the hippocampal brain-derived neurotrophic factor mRNA levels [ 9 , 10 ]. At present, licensed drugs include cholinesterase inhibitors (donepezil, rivastigmine, and galantamine) and a glutamate NMDA ( N -methyl- d -aspartate) receptor antagonist (memantine) [ 4 , 11 ]; a range of other nonspecific drugs often prescribed include tranquilizers, antipsychotics, antidepressants, and hypnotics.…”
Section: Introductionmentioning
confidence: 99%
“…The use of traditional Chinese medicine (TCM) has a long history and was first documented by the Sheng Nong Classic of Materia Medica. Currently, traditional Herbal Medicines (THM) are widely used in cardio-cerebrovascular, endocrine, gastrointestinal, neuropsychiatric, and respiratory disorders (Dai et al, 2018;Jiang et al, 2019;Kong et al, 2019;Qin et al, 2019;Gao et al, 2020;Liu et al, 2020;Zhang et al, 2020). Several studies have evaluated the efficacy and safety of THM in treating GERD (Ling et al, 2015;Dai et al, 2017;Shih et al, 2019).…”
Section: Introductionmentioning
confidence: 99%